2008
DOI: 10.1103/physrevb.77.245313
|View full text |Cite
|
Sign up to set email alerts
|

Transport through a double-quantum-dot system with noncollinearly polarized leads

Abstract: We investigate linear and nonlinear transport in a double quantum dot system weakly coupled to spin-polarized leads. In the linear regime, the conductance as well as the nonequilibrium spin accumulation are evaluated in analytic form. The conductance as a function of the gate voltage exhibits four peaks of different height, with mirror symmetry with respect to the charge neutrality point. As the polarization angle is varied, due to exchange effects, the position and shape of the peaks change in a characteristi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 56 publications
2
74
0
Order By: Relevance
“…Spin degeneracies can be neglected in the presence of unpolarized or collinearly polarized leads. 30,39 Orbital degeneracies are system dependent and they are not present in the single and double quantum dot systems discussed in this paper. A detailed discussion of their effects can be found, for example, in Refs.…”
Section: Transport Through Multiple Quantum Dot Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Spin degeneracies can be neglected in the presence of unpolarized or collinearly polarized leads. 30,39 Orbital degeneracies are system dependent and they are not present in the single and double quantum dot systems discussed in this paper. A detailed discussion of their effects can be found, for example, in Refs.…”
Section: Transport Through Multiple Quantum Dot Devicesmentioning
confidence: 99%
“…29,30 In the second part, the case of independently coupled dots is discussed, where the detuning of the two gate voltages influences the level spacing of the energy spectrum. Thus, excited states can be observed only in detuning ranges where the difference between the energy level of the excited state and its ground state is less than 2| |.…”
Section: B the Double Quantum Dotmentioning
confidence: 99%
See 1 more Smart Citation
“…Spin-dependent level shifts can originate to the lowest order in the tunneling Hamiltonian (sequential tunneling limit) if off-diagonal elements of the reduced density matrix participate in the dynamics. This is the case for noncollinearly polarized leads 14,16,17 but also for collinearly polarized leads for some double-dot setups. 18 Here we consider situations where coherences of the reduced density matrix do not play a crucial role in the dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…(A.3-14), we found that the one-particle retarded GF can be simply decomposed into a sum of contributions from eight spin-charge configurations of the SCQD system in the condition of t 12 /U ℓ ≪ 1 (after ignoring those small contributions proportional to t 12 /U .). It reads 15) where P m = p m 0 ; p m 's are probability weights defined in Eq. (3).…”
Section: Appendix Amentioning
confidence: 99%